„Ни на кого надеи не маю, толко на милосердного Бога да на вашу милость“: Letters of Lithuanian Nobles, Addressed to a Monarch’s Clerk Jonas Bogdanaitis Sapiega, [1507]–[1515] - Ryčkov, Andrej (Lietuvos istorijos studijos, 2018)
[text in Lithuanian]
Keywords: none